Penerapan Metode Analitycal Hierarchy Process (AHP) dalam Menentukan Judul Skripsi - Joko Syahputra; Alex Rikki (Yayasan Kita Menulis, 2020)
Thesis is a requirement to obtain undergraduate status (S1) in every university in Indonesia. The term thesis as an undergraduate final project is only used in Indonesia. To complete the thesis, students are required to apply what they learn into an application or application in certain fields, both learning and in the form of computer applications. Analytical hierarchy process (AHP) is a general theory of measurement used for scale ratios, both from discrete and continuous pairwise comparisons. Analytical hierarchy process (AHP) can simplify complex and unstructured, strategic and dynamic problems into its parts, and make variables in a hierarchy (level) the Analytical hierarchical process (AHP) method has the ability to solve multi-objective problems based on comparisons preferences of each element and hierarchy.